Transcription regulation of Nrp1 during endothelial cell differentiation - Zhao, Z (2014)
Various diseases, including cancer, stroke and heart attack, are associated with disruption of the vascular system. However, lack of a profound understanding of the transcription regulation during vascular development hinders the formation of effective molecular intervention strategies targeting angiogenesis. Here we describe an enhancer of Neuropilin1 (Nrp1) from the second intron of the gene that directs arterial and coronary endothelial cell-specific expression. Mice transgenic for either human or mouse sequences of the Nrp1in2 enhancers drove expression of the LacZ reporter gene specifically in the endothelial cells within the arterial compartment from early in development, while no expression was detected in veins. In addition, the hNrp1in2 enhancer directed expression to the endothelial cells in the developing coronary vasculature, with the initial expansion from around the sinus venosus at E11.5, and eventually contributed to the capillary, venous and arterial compartments of the coronary vessels but not the endocardium. This expression pattern is consistent with that reported in the Apelin-nlacZ line (Red-Horse et al., 2010), making the Nrp1 enhancer the first identified mammalian regulating enhancer of the coronary endothelial cell. Phylogenetic footprinting, and a tissue culture reporter assay suggested that this enhancer contains a 184bp minimal core region hNrp1in2peakA2 that recapitulates the expression profile of the full length enhancer. hNrp1in2peakA2 has conserved and in vitro validated recognition sites for Gata, Ets, and Fox. The validated Fox and Ets sites form a functional FOX:ETS motif, and the FOX:ETS motif is responsible for synergistic activation ofthe enhancer by FoxC2 and Etv2 in reporter assays. Mutation introduction to the functional Ets sites or compound ablation of the Gata and Fox site in hNrp1in2peakA2 result in total loss of vascular expression, in terms of both arterial and coronary expression. The Fox, Ets and Gata recognition sites may be sufficient to achieve arterial- and coronary- specific expression of the hNrp1in2peakA2.